2021
DOI: 10.3389/fpsyg.2021.622842
|View full text |Cite
|
Sign up to set email alerts
|

Global Citizens – Global Jet Setters? The Relation Between Global Identity, Sufficiency Orientation, Travelling, and a Socio-Ecological Transformation of the Mobility System

Abstract: Global crises such as the climate crisis require fast concerted action, but individual and structural barriers prevent a socio-ecological transformation in crucial areas such as the mobility sector. An identification with people all over the world (i.e., global identity) and an openness toward less consumption (i.e., sufficiency orientation) may represent psychological drivers of a socio-ecological transformation. We examined the compatibility of both concepts as well as their relation to people’s support of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 85 publications
1
30
2
Order By: Relevance
“…Researchers have argued that identification with all humanity might be a pathway towards addressing global (and socially unjust) environmental threats such as climate change because people strive for the well-being of their ingroups (e.g., Reese, 2016). Indeed, several prior studies have shown that global identity is positively related to proenvironmental behavior and policy support (e.g., Joanes, 2019;Loy & Reese, 2019;Loy et al, 2021;Renger & Reese, 2017).…”
mentioning
confidence: 99%
“…Researchers have argued that identification with all humanity might be a pathway towards addressing global (and socially unjust) environmental threats such as climate change because people strive for the well-being of their ingroups (e.g., Reese, 2016). Indeed, several prior studies have shown that global identity is positively related to proenvironmental behavior and policy support (e.g., Joanes, 2019;Loy & Reese, 2019;Loy et al, 2021;Renger & Reese, 2017).…”
mentioning
confidence: 99%
“…One explanation for the ambiguity of our findings with the literature may be that sufficiency orientation and materialism may not be related as we assume throughout this paper and as conceptual research suggests [36,[116][117][118]. One reason might be that contemporary consumerism is more focused on services or areas of consumption that are not directly material (e.g., carbonized mobility practices [24,25] or digitalization [38]). Materialism measures do not necessarily capture these carbon-intensive consumption practices.…”
Section: Increase In Sufficiency Orientation After Study Participationmentioning
confidence: 75%
“…A reorganization of society in line with the sufficiency principle requires individuals who are open to rethink values and aspirations and develop a sufficiency orientation themselves. In line, sufficiency at the individual level represents a voluntary strategy to reduce consumption (e.g., [23]) in high-impact fields of action (e.g., see Loy et al [24] on flying and sufficiency orientation, see also Verfuerth et al [25]). In the German debate on adequate sustainability strategies, sufficiency is often criticized, partly out of fear that it might trigger feelings of loss and aversion (see Gossen et al [26] on how to communicate sufficiency in marketing strategies).…”
Section: Sufficiency Orientation As Multidimensional Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to achieve such transformation, there is still the need to systematically connect psychological theories and embed them in interdisciplinary research at the intersection with, e.g., political change (Wullenkord and Hamann 2021). Specifically related to the transformation of socio-ecological systems, a perspective on identities puts particular attention to the existence of a global identity (Loy et al 2021), often defined as a "shared identity as human beings" (Manuel-Navarrete and Buzinde 2010, p. 143), or on collective identities resulting from local place attachment (Escalera-Reyes 2020) to effect climate action.…”
Section: Social Identities In Climate Actionmentioning
confidence: 99%